CONTINUOUS INTEGRATION PIPELINE WITH JENKINS - Alexander, Alexander; Wella, Wella (Jurnal Pilar Nusa Mandiri, 2025)
The advancement of technology has led to continuous improvement in application development. As a result, there is a growing demand for application software. Tech companies are constantly working on building and updating their existing applications. The development process is prolonged because to the intricate nature of the build and deployment procedures, ensuring that the application software can be accessed and utilized by individuals across the internet. To address these issues, this research aims to construct and enhance a system capable of automating the entire build and deployment process. By eliminating human intervention, potential errors and downtime that may prevent access to the deployed application can be avoided. The system was developed using the RAD or Rapid Application Development method, with the goal of simplifying and expediting the development process. A DevOps Engineer facilitates the implementation of Continuous Integration in order to reduce the duration of the entire Software Development Life Cycle (SDLC) by utilizing an open-source tool named Jenkins. This ensures that the application development process is efficient and adheres to the designated schedule, allowing all users to benefit from timely delivery.